Is Islamic Philosophy ‘Islamic’? : A Critical Exploration Through the Qur'anic Narratives - Dhulkifli, Muhammad Luthfi (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
This paper critically examines the ongoing debate surrounding the Islamic nature of Islamic philosophy by engaging with key Qur'anic narratives and philosophical discourses. The central question addressed is whether Islamic philosophy can genuinely be classified as “Islamic”, considering its amalgamation of Greco-Roman and Persian intellectual traditions. In common, Islamic philosophy addresses themes familiar to broader philosophy, but it does so from an Islamic perspective, using the language and context of Islamic civilization. By analyzing the works of prominent Muslim philosophers, including al-Farabi, Ibn Sina, and al-Ghazali, the study explores how their interpretations and methodologies align—or diverge—from the foundational texts of Islam. Additionally, this paper highlights how Qur'anic narratives have been employed within Islamic philosophical thought to construct ethical, metaphysical, and theological frameworks. In conclusion, the “philosophical discussion of Islamic issues” is considered to be representative term for Islamic philosophy as it captures its essence and clarifies debates about its origins, actors, and focus discussions.